Application of Dry Probiotic Rabal to Increase Growth Performance of Catfish (Clarias sp.) - Lukman Anugrah Agung; Imas Rohmawati (Jurnal Biologi Tropis, 2021)
Catfish have become an important contributor to fish production in Indonesia. Catfish consumption in Indonesia always increases every year. To meet the demand for catfish consumption, it was carried out with an intensive aquaculture system. However, the high cost of feed has been identified as a significant constraint in catfish farming. Efforts to increase catfish growth are needed to reduce feed costs, one of the efforts is by probiotic supplementation through the feed. This study was carried out to determine the best dose of probiotic rabal dried addition to increasing catfish growth. The experiment used four treatments and three replications. Probiotic rabal dried doses: 0% of feed (A)/feed (control), 5% of feed (B), 10% of feed (C), and (D) 15% of were used as treatment. The feed was given ad-satiation with a frequency of feeding three times a day. Observations were made for 45 days. The results indicated that the B treatment of 5% of feed gave the best absolute weight growth and feed conversion ratio. While catfish fish survival rate was not significantly different on all treatments.